DIGITAL PORTFOLIOS IN VOCATIONAL SPEAKING CLASSES: TEACHER’S PERCEPTIONS AND LESSON PLAN ANALYSIS - Zainiza, Mailiza; Trisanti, Novia (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
Digital portfolios have become increasingly relevant in language education as tools for documenting learning processes, enabling multimodal task performance, and supporting formative assessment. However, limited research has examined how they are embedded in instructional planning or how teachers perceive their assessment role, especially in vocational English classrooms. This qualitative case study investigates (1) how digital portfolios are integrated into a speaking lesson plan, and (2) how a vocational English teacher perceives their use as an assessment tool. Data were collected through document analysis and an open-ended teacher questionnaire completed by an English teacher in an Indonesian vocational high school. The data were analyzed using thematic analysis. The findings show that digital portfolios were positioned as central to the design of speaking tasks, functioning as a structured mechanism for organizing workflow, documenting progress, and compiling multimodal evidence of learning. The teacher perceived the portfolio as a valuable tool for monitoring engagement, identifying learners who need support, and enhancing transparency in the learning process. However, constraints related to the absence of explicit assessment rubrics, increased workload, and varying student digital literacy limited the portfolio’s potential for systematic assessment of speaking skills. The study concludes that digital portfolios have strong potential as process-based assessment tools in vocational English instruction; however, their effectiveness depends on the availability of clear assessment criteria, technological readiness, and sustained institutional support.